THE EFFECT OF GRAPHENE OXIDE ADDITION ON MAGNETIC PROPERTIES OF IRON OXIDE (FE2O3) NANOPOWDER WITH SINTERING AND NON-SINTERING PROCESS - Cepi Yazirin; A. Muhammad; J. W. Dika; D. I. Tsamroh; Mudawamah Mudawamah (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2021)
Graphene Oxide is a material that has a thickness of one atom composed of carbon atoms to form a hexagonal lattice and a material that has unique properties, namely mechanical, optical, thermal, and electrical properties. Fe2O3 is a material that has magnetic properties and can be used for various applications such as enzyme separation, drug transport, microwave absorption, photocatalysts, biological applications, biomedicine, metal separation, and magnetic resonance imaging (MRI). In this study, the addition of graphene oxide was carried out using the coprecipitation method on Fe2O3 nanomaterials that had been treated with sintering and non-sintering. The coprecipitation method is the synthesis of inorganic compounds which is based on the deposition of more than one substance together when it passes the saturation point. The purpose of this study was to determine whether the addition of graphene oxide to the Fe2O3 material can increase the magnetic properties of the Fe2O3 material or vice versa. The result was that the sintering treatment on Fe2O3 GO did not have a transforming effect on its magnetic properties, but instead had a changing effect on its magnetic value. However, the magnetic coercivity value of Fe2O3 + GO 700 ºC increased to 0.038 Tesla. Thus, it can be concluded that at a temperature of 700 °C graphene oxide acts as a barrier from external magnetic fields in the opposite direction.